Enchancing Science Learning Outcomes through the Snowball Throwing Strategy: A Classroom Action Research in Indonesian Primary Schools - Rahmawati, Anik; Setiyawati, Dewi (Yayasan Darussalam Bengkulu, 2023)
This study examines the effectiveness of the Snowball Throwing cooperative learning strategy in improving science learning outcomes among fourth-grade students at MI Ma’arif Pabelan, Central Java, Indonesia. A classroom action research design was applied over three cycles, each consisting of planning, implementation, observation, and reflection. The participants included 33 students (22 males and 11 females). Data were gathered through achievement tests, structured observations, and documentation, and were analyzed using descriptive statistics. The results revealed steady improvements in student mastery: 51.51% in Cycle I, 69.69% in Cycle II, and 87.87% in Cycle III, surpassing both the minimum competency standard (65) and the classical completeness benchmark (85%). These findings confirm that Snowball Throwing is effective in enhancing engagement and learning achievement, especially in teaching conceptually abstract science topics such as the Earth’s appearance and celestial motion. The study contributes to the literature by documenting iterative improvements across multiple cycles, highlighting its applicability in underrepresented contexts such as Islamic elementary schools. Beyond affirming the value of cooperative learning, this research emphasizes the importance of reflective teaching practices and iterative instructional refinement in achieving sustainable improvements in science education.